Bacillus cytotoxicus Isolated from a Pristine Natural Geothermal Area Reveals High Keratinolytic Activity - Cavello, Ivana Alejandra (2020)
Geothermal areas are the niches of a rich microbial diversity that is not only part of the intangible patrimony of a country but also the source of many microbial species with potential biotechnological applications. Particularly, microbial species in geothermal areas in Argentina have been scarcely explored regarding their possible biotechnological uses. The purpose of this work was to explore the proteolytic and keratinolytic enzymatic potential of microorganisms that inhabit in the Domuyo geothermal area in the Neuquén Province. To this end, we did enrichment cultures from two high-temperature natural samples in mineral media only supplemented with whole chicken feathers. After the isolation and the phylogenetic and morphologic characterization of different colonies, we obtained a collection of Bacillus cytotoxicus isolates, a species with no previous report of keratinolytic activity and only reported in rehydrated meals connected with food poisoning outbreaks. Its natural habitat has been unknown up to now. We characterized the proteolytic and keratinolytic capacities of the B. cytotoxicus isolates in different conditions, which proved to be remarkably high compared with those of other similar species. Thus, our work represents the first report of the isolation as well as the keratinolytic capacity characterization of strains of B. cytotixicus obtained from a natural environment.